Interactive effects of ocean acidification and rising sea temperatures alter predation rate and predator selectivity in reef fish communities. (30th January 2015) - Ferrari, Maud. C. O.; Munday, Philip L.; Rummer, Jodie L.; McCormick, Mark I.; Corkill, Katherine; Watson, Sue‐Ann; Allan, Bridie J. M.; Meekan, Mark G.; Chivers, Douglas P.
Abstract: Ocean warming and acidification are serious threats to marine life. While each stressor alone has been studied in detail, their combined effects on the outcome of ecological interactions are poorly understood. We measured predation rates and predator selectivity of two closely related species of damselfish exposed to a predatory dottyback. We found temperature and CO2 interacted synergistically on overall predation rate, but antagonistically on predator selectivity. Notably, elevated CO2 or temperature alone reversed predator selectivity, but the interaction between the two stressors cancelled selectivity. Routine metabolic rates of the two prey showed strong species differences in tolerance to CO2 and not temperature, but these differences did not correlate with recorded mortality. This highlights the difficulty of linking species‐level physiological tolerance to resulting ecological outcomes. This study is the first to document both synergistic and antagonistic effects of elevated CO2 and temperature on a crucial ecological process like predator–prey dynamics.